The philosophy of Aristotle : a selection with an introduction and commentary by Renford Bambrough ; with a new afterword by Susanne Bobzien ; Translations by J.L. Creed and A.E. Wardman. - Aristotle (Signet Classic., 1963)
More than two thousand years ago, Aristotle established unique standards of philosophic inquiry, observation, and judgment. This book offers a contemporary reevaluation of the philosophy of the master of Western thought, and shows his vital, continuing influence in our modern world.